Distribution of different forms of phosphorus in calcareous soils from middle and south of Iraq - Makttoof E.A.; Kassim J.K.; Khuzale K.H (Al-Qadisiyah Journal For Agriculture Sciences, 2020)
A survey of the chemical way to determine the amount of different phosphorus forms in calcareous soils was carried out on 22 calcareous soils fertilized for many years with phosphate fertilizers from central and southern Iraq. Extraction methods were developed by combining the technique of individual traditional methods of different forms with sequentially extraction technology. Soil samples were collected from surface (0-30 cm) and subsurface (30-60 cm) horizons. Forms of soluble, ready available, organic and total phosphorus were extracted independently and in addition to the successive extraction were carried out according to Jiang and Gu (1989) method. The amount of soluble and available phosphorus extracted were low and ranged from 0.17 to 2.12 mg kg-1 and 7.28 and 34.3 mg kg-1 respectively. Organic phosphorus was medium and the values ranged 30.9 and 93.1 mg kg-1 while the total phosphorus content was high and the values ranged between 206.9 and 570.6 mg kg-1. The quantities of phosphorus extracted sequentially by chemical extracts and the possibility of diagnosing different forms of phosphorus associated with calcium Ca2-P, Ca8-P and Ca10-P (apatite) in addition to P associated with OM and free iron and aluminum oxides. The average values of Ca2-P, Ca8-P, Fe-P and occluded (O-P) extracted were nearly similar and the values were 20.47, 25.28, 25.4, and 26.23 mg kg-1 respectively while the Ca10-P was much higher (194.54 mg kg-1) than the other forms.